2016
DOI: 10.1016/j.jpsychires.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a HTR2B stop codon and testosterone on energy metabolism and beta cell function among antisocial Finnish males

Abstract: Herein, we examined insulin resistance (IR), insulin sensitivity (IS), beta cell activity, and glucose metabolism in subjects with antisocial personality disorder (ASPD), and whether the serotonin 2B (5-HT2B) receptor and testosterone have a role in energy metabolism. A cohort of subjects belonging to a founder population that included 98 ASPD males, aged 25-30, was divided into groups based on the presence of a heterozygous 5-HT2B receptor loss-of-function gene mutation (HTR2B Q20*; n = 9) or not (n = 89). Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In vitro results regarding the Htr2 family are more in line with the anticipated mechanism of action; as these receptors couple to Gα q protein following intracellular activation of the phospholipase C pathway, with a subsequent increase in intracellular Ca 2+ , an increase in insulin secretion would hence be anticipated following activation of the Htr2 family, and antagonist treatment would inhibit insulin release. Corroborating in vitro results, it was recently shown that humans carrying a loss‐of‐function mutation in the HTR2B gene (HTR2B Q20*) secrete less insulin compared with non‐carriers after an oral glucose load . This suggests that loss of Htr2b influences insulin secretion in vivo in humans.…”
Section: Introductionmentioning
confidence: 91%
“…In vitro results regarding the Htr2 family are more in line with the anticipated mechanism of action; as these receptors couple to Gα q protein following intracellular activation of the phospholipase C pathway, with a subsequent increase in intracellular Ca 2+ , an increase in insulin secretion would hence be anticipated following activation of the Htr2 family, and antagonist treatment would inhibit insulin release. Corroborating in vitro results, it was recently shown that humans carrying a loss‐of‐function mutation in the HTR2B gene (HTR2B Q20*) secrete less insulin compared with non‐carriers after an oral glucose load . This suggests that loss of Htr2b influences insulin secretion in vivo in humans.…”
Section: Introductionmentioning
confidence: 91%